Leadership Management of The Head of Madrasah - Tukiran Tukiran (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Leadership is the main determinant of the birth process of the dynamics of an education and the effectiveness of leadership. The importance of effective management in educational organizations is getting more and more attention from various parties. Educational institutions will be required to provide effective educational services to students and to the community. The head of the madrasa is the driving force for madrasa resources, especially teachers and madrasa employees. Principal leadership management gives freedom to every school principal (madrasah) to emphasize and prioritize certain competencies in accordance with the vision, mission of the school and their respective regions. Once the importance of the leadership role and the position of the principal or madrasah principal in improving the quality of schools and the quality of students in particular, there must be a continuous effort to evaluate and observe whether school principals have played a good role so that they can present themselves as effective leaders.